PENYEBARAN POPULASI HAMA Paraeucosmetus sp. DI KABUPATEN MINAHASA TENGGARA - Salaki, Christina; Senewe, Emmy (Universitas Sam Ratulangi, 2012)
ABSTRACT Insects Paraeucosmetus sp. Brazilians is a destructive pest of rice grain content of the rice plant to mature milk. Population and the level of this pest has spread in several locations rice production centers. This study aims to determine the spread and intensity of pest populations Paraeucosmetus sp. in rice plants by altitude in Southeast Minahasa district (District Ratatotok Ratahan and Tombatu). The study used purposive sampling method at altitude 0-300 m asl, 301-600 m above sea level and> 601 m asl. The results showed that the presence of pests Paraeucosmetus sp. spread evenly by altitude in Southeast Minahasa regency with the intensity of attacks categorized as mild attacks. Keywords: Distribution of population, Paraeucosmetus sp.